Extracellular Microvesicle Production by Human Eosinophils Activated by “Inflammatory” Stimuli - Akuthota, Praveen; Carmo, Lívia A. S.; Bonjour, Kennedy; Murphy, Ryann O.; Silva, Thiago P.; Gamalier, Juliana P.; Capron, Kelsey L.; Tigges, John; Toxavidis, Vasilis; Camacho, Virginia; Ghiran, Ionita; Ueki, Shigeharu; et al. (Frontiers in Cell and Developmental Biology, 2016)
A key function of human eosinophils is to secrete cytokines, chemokines and cationic proteins, trafficking and releasing these mediators for roles in inflammation and other immune responses. Eosinophil activation leads to secretion of pre-synthesized granule-stored mediators through different mechanisms, but the ability of eosinophils to secrete extracellular vesicles (EVs), very small vesicles with preserved membrane topology, is still poorly understood. In the present work, we sought to identify and characterize EVs released from human eosinophils during different conditions: after a culturing period or after isolation and stimulation with inflammatory stimuli, which are known to induce eosinophil activation and secretion: CCL11 (eotaxin-1) and tumor necrosis factor alpha (TNF-α). EV production was investigated by nanoscale flow cytometry, conventional transmission electron microscopy (TEM) and pre-embedding immunonanogold EM. The tetraspanins CD63 and CD9 were used as EV biomarkers for both flow cytometry and ultrastructural immunolabeling. Nanoscale flow cytometry showed that human eosinophils produce EVs in culture and that a population of EVs expressed detectable CD9, while CD63 was not consistently detected. When eosinophils were stimulated immediately after isolation and analyzed by TEM, EVs were clearly identified as microvesicles (MVs)outwardly budding off the plasma membrane. Both CCL11 and TNF-α induced significant increases of MVs compared to unstimulated cells.TNF-α induced amplified release of MVs more than CCL11. Eosinophil MV diameters varied from 20-1000 nm. Immunonanogold EM revealed clear immunolabeling for CD63 and CD9 on eosinophil MVs, although not all MVs were labeled. Altogether, we identified, for the first time, that human eosinophils secrete MVs and that this production increases in response to inflammatory stimuli. This is important to understand the complex secretory activities of eosinophils underlying immune responses. The contribution of the eosinophil-derived MVs to the regulation of immune responses awaits further investigation.